Intellectual capital disclosure among Malaysian Government-Linked Companies (GlCS) / Musliha Musman and Rashidah Abdul Rahman - Musman, Musliha; Abdul Rahman, Rashidah (Faculty of Accountancy, 2013)
This study aims to examine the level of intellectual capital disclosure among listed Malaysian GLCs by comparing them with the Non-GLCs for the period 2007-2009. Content analysis is used to extract the intellectual capital disclosure items from the annual report. The level of intellectual capital is measured with proxies for categories of human, structural and relational capital. The result shows that the GLCs disclose more intellectual capital information than Non-GLCs. This supports the stakeholders’ theory as GLCs call to provide wider information to the stakeholders especially to the public. For GLCs, relational capital is the most reported category, followed by structural capital. In contrast, Non-GLCs disclose their relational and structural capital equally. The result shows that both GLCs and Non-GLCs disclose at least the human capital.